1937
DOI: 10.1111/j.1744-7348.1937.tb05044.x
|View full text |Cite
|
Sign up to set email alerts
|

Soil Protozoa; Their Growth on Various Media

Abstract: THE methods at present used for the determination of the number and species of soil Protozoa are open to criticism, and it was with the hope of improving this technique that the present investigation was undertaken.The usual method of using peptone agar as a medium for the growth of the Protozoa w&s criticized by Frangois Perey(4) in 1925 when she made duplicate counts from a French garden soil, using peptone agar, and also an agar medium made from B decoction of the same soil. The numbers she obtained with th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

1939
1939
2010
2010

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(3 citation statements)
references
References 5 publications
0
3
0
Order By: Relevance
“…Follow-up experiments in the present study attributed the insignificant protozoan contribution to their low abundance level and limited growth potential in beach sand. Previous studies have reported much smaller protozoan abundances in sandy soils than in other types of soil (Dixon, 1936), implicating grain sizes as a factor. The soil organic content also controls protozoa abundance and activities (Anderson, 2005).…”
Section: Discussionmentioning
confidence: 83%
“…Follow-up experiments in the present study attributed the insignificant protozoan contribution to their low abundance level and limited growth potential in beach sand. Previous studies have reported much smaller protozoan abundances in sandy soils than in other types of soil (Dixon, 1936), implicating grain sizes as a factor. The soil organic content also controls protozoa abundance and activities (Anderson, 2005).…”
Section: Discussionmentioning
confidence: 83%
“…The second method is to use an enriched culture. Sandon ( 1927) found that different culture medias gave rise to different faunas and this was confirmed by Dixon 1937). She found that with different media (peptone agar, soil extract and hay infusion) the peptone favoured specialized species of bacteria and protozoa, where as soil extract permitted growth of many species in small numbers.…”
Section: Culture Experimentsmentioning
confidence: 92%
“…Therefore, samples must be cultured to determine their growth under varying conditions. Several workers have proposed and successfully used different media to culture amoebae isolated from all probable sources of natural environments (Adams 1959;Bovee and Sawyer 1979;Chang 1958;Davis et a/ 1978;Dixon 1937;Fulton 1970;Menapace et al1975;Page 1967Page , 1970Prescott 1956;Prescott and James 1955;Sawyer 1971Sawyer , 1975Singh 1945Singh , 1955.…”
Section: Introductionmentioning
confidence: 99%